Implementation Pre-Marriage Guidance for Brides and Grooms to Minimize Number of Divorces - Musyafa'ah, Nur Lailatul; Fajar, Amelia Rozidatul; Ashari, Asyrof Khanif; Ashari, Lailatus Syarifah (Al-Misbah : Jurnal Islamic Studies (Yogyakarta. Online), 2022)
Marriage is a sacred bond between husband and wife to live happily. However, many couples end up divorcing due to various factors such as disputes, economics, etc. For this reason, the Government conducts guidance on pre-marriage guidance to minimize divorce cases. This Article reviewed the implementation of pre-marriage guidance in the Office of the Ministry of Religious Affairs of Surabaya City to prepare brides and grooms for married life. This research is field research and qualitative. Data collection is conducted by observation, interview, and documentation. The data is then presented, analyzed, and concluded by a deductive analogy. This research concluded that the implementation of pre-marriage guidance in the Office of the Ministry of Religious Affairs of Surabaya City follows the Decree of the Director-General of Islamic Community Guidance No. 379 of 2018 concerning the implementation of pre-marriage guidance. In 2020, they held 28 pre-marriage guidance activities. Pre-marriage guidance is done to prepare the brides and grooms to live in harmony to reduce the occurrence of divorce. However, the implementation could be more optimal due to several factors, including funding, human resources, lack of coordination with several institutions, and awareness of brides and grooms to follow marriage guidance. This research contributes to the importance of the role of Pre-Marriage Guidance for Brides and Grooms as the foundation of the family. The debate about roles and barriers is discussed in this article.